Carbon sink strength of a Mediterranean cork oak understorey: how do semi-deciduous and evergreen shrubs face summer drought? - Correia, A. C.; Costa e Silva, F.; Correia, A. V.; Hussain, M. Z.; Rodrigues, A. D.; David, J. S.; Pereira, J. S. (Journal of Vegetation Science, 2013)
Questions How do semi-deciduous and evergreen shrubs exploit environmental resources during summer drought? What is the contribution of the understorey shrubby layer to ecosystem carbon assimilation? To what extent are carbon balance and transpiration impacted by a rain pulse? Location Cork oak open woodland in the Mediterranean region. Methods We used closed dynamic light and dark chambers to measure gas exchange (CO2 and H2O) in the dominant shrub understorey species Cistus salviifolius, Cistus crispus (semi-deciduous) and Ulex airensis (evergreen), together with plant physiological and morphological measurements during summer drought and autumn recovery. A hyperbolic light response model constrained by vapour pressure deficits was fitted for up-scaling shrub photosynthesis to the ecosystem level. The data were compared, on a daily and daytime basis, with gross primary productivity estimates from ecosystem eddy-covariance flux measurements. Results The onset of summer drought led to a significant leaf area reduction in semi-deciduous species. A general decrease in photosynthesis in all species was observed, while evapotranspiration and above-ground respiration fluxes contrasted among species during summer progression and autumn recovery. The shallow-rooted C. salviifolius was able to use light more efficiently than the other two species, although with poor stomatal control over water loss and consistently higher above-ground respiration rates, leading to lower water and carbon use efficiencies when compared with C. crispus. The deep-rooted shrub U. airensis maintained higher leaf water potentials and very low photosynthetic rates while decreasing transpiration rates throughout the summer drought. A summer rain pulse showed that shallow-rooted shrubs use water in an opportunistic way, with immediate leaf rehydration and concomitant photosynthesis increments. Conversely, deep-rooted shrubs (U. airensis) were unresponsive, only recovering photosynthesis with high soil water content. An opportunistic growth response may be disadvantageous to shallow-rooted shrubs in a future climate with extended dry summers and higher probability of rain pulse events. The prominent increase in transpiration rates and plant respiration costs observed during the dry conditions that followed the rain pulse, led to a reduced plant ability to recover after autumn rains. Conclusions The shrubs that naturaly colonized this montado understorey showed contrasting strategies to overcome summer drought, suggesting an efficient mosaic exploitation of seasonal environmental resources. The contribution of these shrubs to total ecosystem CO2 uptake during summer and autumn recovery was 17%. This high contribution implies that shrub density management decisions should consider a carbon balance perspective.
Keywords: Cistus sp; CO2; Eddy-covariance; H2O; Mediterranean; partitioning; Shrubs; Ulex sp; up-scaling

Herbaceous layer development during spring does not deplete soil nitrogen in the Portuguese montado - Otieno, D. O.; Mirzaei, H.; Hussain, M. Z.; Li, Y. L.; Schmidt, M. W. T.; Wartinger, M.; Jung, E.; Ribeiro, N.; Pereira, J. S.; Tenhunen, J. (Journal of Arid Environments, 2011)
Nitrogen (N) content in the soil and in the herbaceous biomass were monitored during spring of 2004e2006 to determine how the herbaceous layer development inﬂuences soil N availability in the montado ecosystem of southern Portugal. Highest (246.6 52.7 g m2 ) and lowest (123.2 89.5 g m2 ) peak biomass occurred in 2006 and 2005 respectively. Total soil N within the top 20 cm soil proﬁle ranged between 0.2 0.1% in February and 0.41 0.2% in May, while available soil N was lowest (5 2 mg g 1 soil) in February but increased three-to-ﬁve fold in March and was >17.5 mg g 1 soil at senescence in May. Signiﬁcant (p < 0.001) increase in total N in the aboveground pool occurred between February and May. There was however, no decay in soil N content. Instead, the herbaceous vegetation enhanced soil N input and N retention in the ecosystem. Most of the herbaceous plants were annuals with large reserves of organic N at senescence, which returned to the soil as detritus. The herbaceous vegetation is a critical component of the montado that contributes to N recharge and cycling within the ecosystem
Keywords: Biomass development of the herbaceous vegetation; Mediterranean ecosystems; pasture; Plant and soil nitrogen pools; Portuguese montado; Root distribution and nutrient uptake; Soil moisture

Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Rainfall interception by an isolated evergreen oak tree in a Mediterranean savannah - David, T. S.; Gash, J. H. C.; Valente, F.; Pereira, J. S.; Ferreira, M. I.; David, J. S. (Hydrological Processes, 2006)
Redistribution of ground-level rainfall and interception loss by an isolated Quercus ilex tree were measured over 2 years in a Mediterranean oak savannah. Stemﬂow, meteorological variables and sap ﬂow were also monitored. Rainfall at ground level was measured by a set of rain-gauges located in a radial layout centred on the tree trunk and extending beyond the crown limits. Interception loss was computed as the difference between the volume of rainwater that would reach the ground in the absence of the tree and the volume of water that actually fell on the ground sampling area (stemﬂow included). This procedure provided correct interception loss estimates, irrespective of rainfall inclination. Results have shown a clear non-random spatial distribution of ground-level rainfall, with rainwater concentrations upwind beneath the crown and rain-shadows downwind. Interception loss amounted to 22% of gross rainfall, per unit of crown-projected area. Stand interception loss, per unit of ground area, was only 8% of gross rainfall and 28% of tree evapotranspiration. These values reﬂect the low crown cover fraction of the stand (0Ð39) and the speciﬁc features of the Mediterranean rainfall regime (predominantly with few large storms). Nevertheless, it still is an important component of the water balance of these Mediterranean ecosystems
Keywords: interception loss; Isolated trees; Quercus ilex; rainfall interception; rainfall redistribution

Seasonal Variations in Soil and Plant Water Status in a Quercus suber L. Stand: Roots as Determinants of Tree Productivity and Survival in the Mediterranean-type Ecosystem - Otieno, D. O.; Kurz-Besson, C.; Liu, J.; Schmidt, M. W. T.; Do, R. Vale-Lobo; David, T. S.; Siegwolf, R.; Pereira, J. S.; Tenhunen, J. D. (Plant and Soil, 2006)
Studies were conducted to examine changes in soil (Ys) and plant water status during summer in a 16-year old Quercus suber plantation in southern Portugal. Continuous measurements were conducted between May 2003 and August 2004, while discontinuous measurements were conducted on a monthly basis between May and September 2003 and repeated between March and September 2004. Intensive measurements were conducted on ﬁve trees with mean height and DBH of 5.3 m and 11.6 cm, respectively, growing at close proximity to each other. Weather conditions and soil water potential (Ys) at the rhizosphere of each of the trees measured at 0.3 and 1 m soil depth were continuously monitored. Predawn (Ypd) and midday (Ymd) leaf water potentials were determined every month. Soil and plant samples were also collected in June and September from diﬀerent locations within the study site for d 18 O isotope composition analysis. Pressure–volume (p–v) curves were constructed from plant shoots at diﬀerent times during the vegetative period to determine osmotic potential at full saturation (P 100 ), water potential at turgor loss point (Ytlp), relative water content at turgor loss point (R*tlp) and bulk modulus of elasticity (e). Signiﬁcant P < 0.05 decline in Ys occurred between May and September, the lowest value recorded being –2.0 MPa. Decline in soil moisture aﬀected tree water status, but decline in leaf water potential varied signiﬁcantly (P < 0.05) among the trees. At the end of summer drought, lowest Ypd measured was –1.7 MPa while the highest measured during this time was –0.8 MPa. Diﬀerences among trees were attributed to diﬀerences in rooting depth, as shown by regression analysis of 18 O isotopes. Radial stem growth ceased when Ys within the upper 0.3 m depth approached –1.5 MPa. The upper soil layers contributed approximately 33% of the total tree water requirement, between spring and mid summer when drought was experienced by trees. Deep soil layers however, supplied most of the water required during drought and no growth was recorded during this time. Stressed trees increased solute concentration of their tissues by a Magnitude of 0.7 MPa while bulk tissue elastic modulus increased by about 17 MPa. The study emphasizes the signiﬁcance of roots as determinants of tree productivity and survival in the Mediterranean ecosystems.
Keywords: Drought stress; leaf water potential; osmotic adjustment; oxygen isotope; root distribution

Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings - Cerasoli, S.; Scartazza, A.; Brugnoli, E.; Chaves, M. M.; Pereira, J. S. (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.8310.1093/treephys/24.1.83
Keywords: 15N labeling; defoliation; Nitrogen remobilization; starch

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site - FARIA, T.; Cerasoli, S.; García-Plazaola, J. I.; Guimaraes, M. P.; Abadia, A.; Raschi, A.; Miglietta, F.; Pereira, J. S.; Chaves, M. M. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: Elevated CO2; fluorescence; water stress; xanthophylls

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - García-Plazaola, J. I.; FARIA, T.; Abadía, J.; Chaves, M. M.; Pereira, J. S. (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.166710.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M. M.; Pereira, J. S.; Cerasoli, S.; CliftonBrown, J.; Miglietta, F.; Raschi, A.; Chaves J. S. ;Cerasoli, S. ;Clifton Brown (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)The following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD label: Fisiologia - CO2 elevado
Keywords: Elevated CO2; Fisiologia - CO2 elevado; fluorescence; long-term acclimation; stomata; sugars; water deficits

The effect of individual tree shelters in growth and morphology of cork oak seedlings - Dias, A. S.; Tomé, J.; Tavares, P.; Nunes, J.; Pereira, J. S. (SCIENTIA gerundensis, 1992)
To study the effects of the tree shelters in growth and morphology of cork oak ( Quercus suber L.) seedlings two types of plastic shelters were used in this work: A, transparent PVC shelters (brown) reinforced withawhitepolyesternet, 75 cmofheight; B, translucentbrownpolypropilene, double w$led, square cross section and 120 cm of height. The plants were grown in 120 cm long tubes in Evora, Portugal and growth of sheltered and control plants was evaluated based upon measurements of height, branch lenght, number and area of leaves and biomass. Additionally the anatomy and morphology and heat tolerance of leaves of sheltered andcontrolplants was studied. The results sbow that prowth in beight was stimulated by shelters. The amount of branches was greater in seedlings with shelters seedlings in shelters B were not significant. The shootíroot ratio was higher in sheltered plants than in controls because of the above-ground biomass increased in the former whereas root biomass remained unchanged. Foliage developed inside the shelters showed characteristics of acclimation to shade and were less tolerant to heat being killed at lower temperatures than those of unsheltered controls. A than in controls but the differences between the latter and
Keywords: Acclimation to shade; heat tolerance; Quercus suber; tree shelters